Cochlear Implant Outcomes in Neurofibromatosis Type 2: Implications for Management. Issue 4 (April 2021) - Deep, Nicholas L.; Patel, Evan J.; Shapiro, William H.; Waltzman, Susan B.; Jethanamest, Daniel; McMenomey, Sean O.; Roland, John Thomas; Friedmann, David R.
Abstract : Objective: To describe our institutional experience with cochlear implantation (CI) for rehabilitation of hearing loss in Neurofibromatosis type 2 (NF2) patients. Study Design: Retrospective review between 1989 and 2019. Setting: Tertiary-care center. Patients: Twenty-four patients (67% female, mean age 45.6years) with NF2. Management of their ipsilateral vestibular schwannoma included microsurgery (n=12), stereotactic radiation (n=5), and observation (n=7). Interventions: Cochlear implantation. Main Outcome Measures: Ability to obtain open-set speech, daily device usage and long-term device benefit. Results: All patients achieved some degree of sound awareness with CI. Nineteen patients (79%) achieved open-set speech understanding with a mean word-recognition score of 43% (range 0-88%). Patients with tumors 1.5 cm or less demonstrated the better speech understanding, without significant differences among treatment modalities. For tumors greater than 1.5 cm, patients who underwent microsurgery had a lower rate of open-set speech understanding compared to those treated with radiation or observation. Regular daily device use in 83% of patients was found. Long-term use (>10years) was observed in several patients, though some ultimately required reimplantation with an auditory brainstem implant due to progressive tumor growth. Mean follow-up duration was 4.1 years (range 0.4-15). Conclusions: Cochlear implantation can be an effective treatment for hearing loss in NF2 patients provided the cochlear nerve is intact, regardless of prior management for the ipsilateral tumor. The degree of benefit varies and is influenced by tumor size. Management strategies that preserve the cochlear nerve maximize the interval during which a CI could be of benefit to NF2 patients.